Growing through adversity: the relation of early childhood educator post-traumatic growth to young children’s executive function - Clark, Caron A. C.; Hatton-Bowers, Holly; Akhavein, Kimia; Rasby, Sarah; Parra, Gilbert R. (Frontiers in Psychology, 2024)
Introduction Early childhood educators (ECEs) play a critical role in supporting the development of young children’s executive functions (EF). EF, in turn, underpins lifelong resilience and well-being. Unfortunately, many ECEs report adverse childhood experiences (ACEs) that may compound high stress levels associated with an emotionally and physically demanding profession. ACEs have well-established negative implications for adult well-being and may dampen ECEs’ capacities to engage in emotionally responsive interactions with children. However, many individuals who experience ACEs also report post-traumatic growth experiences that foster empathy, self-determination, and resilience. Such post-traumatic growth may equip teachers with skills to engage in responsive interactions with children that support children’s EF. The aim of this study was to explore the relations of ECE ACEs and post-traumatic growth to the EF of children in their classrooms. Methods Fifty-three female ECEs self-reported on their ACEs and post-traumatic growth. Parents of 157 children (53% male, 47% female, M age = 4.38 years) rated children’s EF. Results In a set of linear mixed models that accounted for multiple demographic factors and ECE perceived workplace stressors, ECE ACEs were not significantly related to children’s EF scores. However, controlling for ACEs, higher levels of ECE post-traumatic growth were associated with fewer parent-reported EF difficulties in children. Discussion ECEs may draw on the coping skills they have developed in times of adversity to model and promote healthy EF for children. Mental health supports to facilitate ECEs’ processing of their own trauma may be a fruitful means to foster positive early childhood environments that nurture the well-being and resilience of future generations.